Menggali Potensi Diri Remaja Sebagai Kunci Sukses Masa Depan - Jungjungan Simorangkir; Winarti Agustina; Marina Letera Nababan; May Rauli Simamora (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
The emergence of several incidents and cases regarding deviant behaviors in adolescents is making individuals, parents, and teachers concerned. Several causative factors for deviant behaviors in adolescents include the search for identity, parenting, and so forth. Data from the Central Bureau of Statistics (Statistics Indonesia) states that adolescents’ behaviors tend to lead to crime. This matter encouraged the Student Creativity Program team to hold webinars regarding resilience. In order for adolescents to have resilience in them to deal with problems, it is necessary to look for the potentials they possessed in themselves to be resilient adolescents as well as successful in the future. This event is done in a day with a resource person who is competent in their field. The enthusiasm of the webinar’s participants was very good, as observed from the impressions given by the participants through google form. The participants mentioned that the webinar was beneficial in increasing their knowledge regarding resilience and allowed them to consult problems up to the exploration of self-potentials. Several recommendations are given to the Student Creativity Program team to continue the event in the form of other webinars.